HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF PADA KURIKULUM MERDEKA TERHADAP MINAT BELAJAR TARIKH SISWA KELAS VII DI MADRASAH TSANAWIYAH LAILATUL QODAR SUKOHARJO - Fatika Salsabila (STKIP Pesisir Selatan, 2026)
This study aims to analyze the relationship between the use of interactive learning media in the Merdeka Curriculum and the interest in learning history among seventh-grade students at Madrasah Tsanawiyah Lailatul Qodar in Sukoharjo. Increasing students’ interest in learning is a crucial aspect in improving the quality of learning at school. To support this increase in interest in learning, teachers have employed various methods, one of which is the use of interactive learning media. In this study, the researcher used a quantitative approach with a descriptive-correlational design, with the research subjects being teachers and students. The researcher used total sampling, or a saturated sample, involving 56 seventh-grade students. Data collection was conducted using a questionnaire. The data were then analyzed using the product-moment correlation technique with the aid of SPSS. The research results—a correlation coefficient of -124 with a significance value of 0.361 (>0.05)—indicate that there is no significant relationship between the use of interactive learning media in the Merdeka Curriculum and the interest in learning history among seventh-grade students at Madrasah Tsanawiyah Lailatul Qodar in Sukoharjo during the academic year. The novelty of this study lies in the finding that the use of interactive learning media does not always increase students’ interest in learning.